Adult ovarian and sellar region mixed germ cell tumor: a case report and literature review - Chen, Dawei; Zhang, Anling; Xue, Kun; Liu, Shuyu; Yan, Xu (Frontiers in Oncology, 2024)
Mixed germ cell tumors (mGCTs) involving both the ovaries and sellar region have been rarely reported; thus, they pose significant challenges in clinical management. Our report of a case of a 26-year-old female with left ovarian mGCTs (dysgerminoma + yolk sac tumor) who presented with postoperative headaches and blurred vision contributes new information to the literature on treating mGCTs, which can lead to standardized regimens and sequencing guidelines. A physical examination revealed right temporal hemianopia, and elevated levels of alpha-fetoprotein were detected in serum and cerebrospinal fluid. Magnetic resonance imaging (MRI) of the sellar region revealed a space-occupying lesion. Pathological examination of the tumor after endoscopic transnasal resection confirmed the diagnosis of mGCTs (germinomas + yolk sac tumor). The patient received adjuvant chemotherapy and radiotherapy at reduced dosages. During follow-up, tumor markers remained within normal limits, and there was no evidence of tumor recurrence on sellar region MRI. This case highlights the rarity of the simultaneous occurrence of ovarian and sellar region mGCTs and emphasizes the importance of accurate diagnosis and multidisciplinary management.